IMPLEMENTASI MODEL KANAL LINTASAN JAMAK PADA SIMULATOR BIDANG DASAR OFDM - , LUTHFI NURMAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Orthogonal Frequency Division Multiplexing (OFDM) is an efficient parallel data transmission scheme. High bit rate can be achieved by sending orthogonal subcarriers. The purpose of this research is to implement an OFDM baseband simulator model. This research is conducted with three computers and soundcard as its interface. The first computer acts as the transmitter, the second computer acts as channel model, and the third computer acts as receiver. This model is carried out with a 16-QAM mapper, 32-point IFFT/FFT, 32 subcarriers (24 data subcarriers, four pilot subcarriers, and four zero subcarriers), and Cyclic Prefix (CP) with Â¼ of OFDM symbol length. The 3rd Generation Partnership Project (3GPP) is used as the standard of multipath with channel model of PA, PB, and VA. To ensure the capability of soundcard sending the signal is good, sample is quintupled to have five repetitions in a series. Symbol detection at the receiver is conducted offline by correlation method. Least Square (LS) algorithm is used for channel estimation. This research analyzes the effect of multipath to the recovered bit and the effect of using LS as channel estimation method. The numerical results are as follows. Without channel estimation, the BERs and MSEs for no multipath are 0.7604 and 0.0837, respectively. The BERs for Pedestrian A (PA), Pedestrian B (PB), and Vehicular A (VA) models are 0.7604, 0.6354, and 0.6563, respectively. The MSEs for PA, PB, and VA models are 0.0757, 0.0529, and 0.0560, respectively. By applying LS channel estimation, the BERs for no multipath, PA, PB, and VA models decreased to 0, 0, 0.1458, and 0.0729, and MSEs decreased to 4.67E-05, 5.92E-05, 0.0219, and 0.0028, respectively.